Effect of Resveratrol on Fatty Acid Compositions and Lipophilic Vitamins of Fructose Induced Nonalcoholic Fatty Liver - Guvenc, Mehmet; Guvenc, Ayse Nilay; Yilmaz, Okkes; Tuzcu, Mehmet (Zoological Soc Pakistan, 2017)
in this study, the effect of resveratrol on the liver of rats induced by fructose was investigated. Adult male Winstar rats were randomly divided into four groups; control, resveratrol, fructose, and resveratrol plus fructose. Resveratrol was administered 30 mg/kg intraperitoneally. Fructose (10% w/v) was administered with drinking water for 56 days every alternate day. Fructose administration increased the hepatic omega-6/omega-3 and 16:1 n7 / 16:0 ratios (p<0.001, p<0.001), but decreased the retinol and alfa tocoferol levels (p<0.01) compared with control group. Resveratrol administration to fructose treated rats decreased the retinol and cholesterol levels (p<0.01, p<0.05), and increased alfa tocoferol and vitamin d(3) levels (p<0.01) in the liver. Our results suggest that resveratrol act as a bioregulator for some biochemical parameters in fructose induced non-alcoholic fatty liver.
Keywords: Resveratroll; Fructose; Fatty acids; Alfa-tocoferoll; Vitamin D3; Cholesterol; Retinol